-(2x+4)=18

Multiply each term in -(2x+4)=18 by -1.

-(2x+4)⋅-1=18⋅-1

Simplify -(2x+4)⋅-1.

Apply the distributive property.

(-(2x)-1⋅4)⋅-1=18⋅-1

Multiply.

Multiply 2 by -1.

(-2x-1⋅4)⋅-1=18⋅-1

Multiply -1 by 4.

(-2x-4)⋅-1=18⋅-1

(-2x-4)⋅-1=18⋅-1

Apply the distributive property.

-2x⋅-1-4⋅-1=18⋅-1

Multiply.

Multiply -1 by -2.

2x-4⋅-1=18⋅-1

Multiply -4 by -1.

2x+4=18⋅-1

2x+4=18⋅-1

2x+4=18⋅-1

Multiply 18 by -1.

2x+4=-18

2x+4=-18

Subtract 4 from both sides of the equation.

2x=-18-4

Subtract 4 from -18.

2x=-22

2x=-22

Divide each term in 2x=-22 by 2.

2×2=-222

Cancel the common factor of 2.

Cancel the common factor.

2×2=-222

Divide x by 1.

x=-222

x=-222

Divide -22 by 2.

x=-11

x=-11

Solve for x -(2x+4)=18